Factors affecting surgical outcome of myringoplasty (Bangladesh Journal of Otorhinolaryngology, 2011)
Introduction: This prospective study was carried out to evaluate the factors that affect the graft take rate as well as hearing improvement after myringoplasty. Method: In this study 60 patients were divided into several groups based on 4 factors like size of perforation (small, medium and large), site of perforation (anterior central, posterior central and central malleolar), Condition of the middle ear (dry & wet) and surgical approach (post auricular and transcanal). Surgical outcome of myringoplasty was measured on the basis of graft take rate and post operative hearing improvement. Results: Size of the perforation affects the graft take rate and post operative hearing gain. Post operative closure of air-bone gap was 10.45 dB, 19.21 dB and 18.86 dB in small, medium and large perforation respectively. Hearing gain was greater after closure of large perforation than the smaller one. Graft take rate was 100%, 82% and 72.73% in small, medium and large perforation respectively. Graft take rate was greater in small perforation than other. Site of perforation also affects surgical outcome after myringoplasty. Graft take rate in anterior central, posterior central and central malleolar perforation was 66.67%, 82.25% and 83.79% respectively. Graft take rate was higher in central malleolar perforation than anterior central perforation. Post operative air-bone gap closure after myringoplasty was 15.31 dB, 12.38 dB and 20.89 dB in anterior central, posterior central and central malleolar perforation respectively. Post operative improvement of hearing was greater in central malleolar perforation. Condition of middle ear at the time of operation also affects the surgical outcome. Graft take rate was 89.36% in dry perforation and 53.85% in wet perforation. Graft take rate was greater in dry perforation. Closure of air-bone gap was 18.23 dB and 7.8 dB in dry and wet perforation respectively. Hearing improvement was greater in dry perforation. No significant difference was found in post-aural and transcanal approach. Conclusion: From this study we concluded that site and size of tympanic membrane perforation and condition of middle ear effects surgical outcome after myringoplasty. Key words: Myringoplasty; hearing improvement; graft take rate. DOI: http://dx.doi.org/10.3329/bjo.v17i2.8846 BJO 2011; 17(2): 82-87